PERTANGGUNGJAWABAN PIDANA TENTANG PENERAPAN UNDANG-UNDANG MENGENAI PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Riski Ani, Riska (Universitas Tadulako, 2024)
The problem of this research is what is the legal position of the perpetrator regarding compensation for land acquisition for development for public purposes from the perspective of state financial losses in criminal acts of corruption and what is the form of criminal responsibility of the applicant in cases of land acquisition for development for public purposes from the perspective of criminal acts of corruption. By using normative research methods. Based on the research results, the legal position of compensation for land acquisition for development for matters of general importance, both payment of physical compensation and payment of non-physical compensation, is in accordance with Article 33 of Law Number 2 of 2012 based on the assessment results of the assessment team as a fair and appropriate assessment. The actor's position as the applicant is not as a legal actor in a corruption criminal case. Development for the public interest from the perspective of criminal acts of corruption cannot be subject to criminal liability to the perpetrator because no state losses were found based on the results of the assessment team's assessment as a fair assessment because all payments received, both for physical losses and non-physical losses, totaled Rp. 2,485. ,903,000.00 (two billion four hundred eighty five million nine hundred three rupiah); is in accordance with Article 33 of Law Number 2 of 2012 concerning Land Acquisition for Development in the public interest.